Improving Skill of SPSS Software For Biology 3rd Year Students of Samara University in 2021: Action Research - Aragaw Asfaw; Abdu Hailu; Hussen Awol (Indonesian Journal of Statistics and Applications, 2022)
SPSS helped revolutionize research practices in the social sciences. Students in Department of Biology think that SPSS statistical software is very difficult for them, because SPSS statistical software is viewed as a hard science than Biology which is viewed as a soft science. The main aim of this action research is to improve the skill of SPSS software’ in the case of biology of third year Biology section A students at the Samara University in 2021. Among all 46, 35 students were included since they are present on the day of training class. The data from the student’s questionnaire were tabulated and analyzed using descriptive statistical method. For the purpose of analyzing the collected data SPSS version 20 software was used. From the summary statistics of the total 35 students the proportion of male and female students is 5(14.3%) and 30(85.7%) respectively. The residence of the student majority 22 (62.9%) comes from rural areas. Of students 23 (65.7%) are motivated for their future research works to use it for statistical data analysis and graphics. There is high demand SPSS training programs for students   as it is mandatory for data analysis. Software training programs like SPSS should be proposed on the curriculum to improve the skill of the students.